Adoption of data-as-a-service by water and wastewater utilities. (April 2023) - Cahn, Amir; Katz, David; Ghermandi, Andrea; Prevos, Peter
Abstract: While technologies in the water sector have been advancing over the past few decades, complementary innovation in business models is needed to support the adoption of these technologies. One emerging opportunity is an outsourced approach to data collection, delivery, and analysis known as "Data-as-a-Service." This study is the first to explore the drivers, barriers, and implementation trends for water and wastewater utilities to adopt this model. The findings provide valuable insights for utility managers looking for new ways to adopt innovative technologies and regulators and policymakers seeking to encourage utilities to make data-driven decisions. Highlights: Data-as-a-Service can facilitate the uptake of innovative solutions within the water sector. The main utility motivations to adopt Data-as-a-Service were ease of operation and reduced risk. Besides having internal solutions, the main barriers were data ownership and security concerns. Wastewater utilities appear to have more complex data management needs than water utilities.